(untitled) - FAO (Rome, 1999)
The book is divided into 4 chapters. Chapter 1 reviews underlying economics and methods of control while specific aspects of high seas fisheries are addressed in Chapter 2. Chapter 3 explores extensively the many issues raised in measuring fishing capacity and capacity utilization; the difficuties associated with assessment of fishing capacity at the global level are brieftly discussed in Chapter4.
Keywords: fisheries